Influence of the freeze-thaw cycles on the physical and mechanical properties of granites - Martins, L. (2016)
Stone masonry buildings provide evidence of the cultural and historical values at the time. Therefore, it is important to preserve the stone of these buildings to harmful environment conditions like freeze-thaw and salt crystallization cycles, air pollution, and excessive and frequent rain or snowfall, which can lead to decay processes that endanger the future of architectural heritage. Thus, it is important to understand how environmental actions act on the physical and mechanical properties of building stones. In Portugal, the most used building stone, particularly in the north region, is granite, both in the vernacular and historical buildings. Therefore, this research aims at evaluating the performance of different types of granite, characteristic of the northeastern region of Portugal to the action of freeze-thaw cycles, for which this environmental action is relevant, given the wide temperature range and the possibility of occurrence of negative temperatures. Frost resistance is important for the durability of the building stone since the freezing-thawing cycles of the water inside the stone pores result in the development of internal stresses, which can lead to cracking and progressive desegregation of material. The analysis of the influence of the freeze and thaw environmental action in the granites belonging to Portuguese vernacular buildings was carried out, based on an enlarged experimental program to obtain the physical and mechanical properties of distinct types of granites before and after the freeze and thaw cycles. This paper presents the experimental campaign of freeze-thaw cycles on three types of granites and discusses the main results analyzing the standard damage indexes associated with the weathering process. Additionally, an analysis of the physical and mechanical properties and the variation of the ultrasonic pulse velocity (UPV) are provided. The freeze-thaw tests showed a considerable influence on the physical properties of granites. The UPV, dry mass, and compressive strength decrease a